ChemInform Abstract: Synthesis, X‐Ray Crystallography, and Reactions of N‐Acyl and N‐Carbamoyl Succinimides. Issue 43 (7th October 2013) - Goodman, Cassie A.; Eagles, Joel B.; Rudahindwa, Leandre; Hamaker, Christopher G.; Hitchcock, Shawn R.
Abstract A series of N‐acyl and N‐carbamoyl succinimides are prepared which are effective reagents for the acylation of primary and secondary amines.